KOSOVO AS A FUTURE MEMBER OF THE WTO - Nagy, Attila (European Scientific Journal, ESJ, 2015)
Kosovo and its citizens need trade liberalization in order to get quality goods and also decrease the imbalance in foreign trade. Recent agreements with the European Union and future trade preferences will certainly help the trade between EU and Kosovo. With this step in hand and the already used CEFTA Agreement Kosovo will be in a much better situation than ever. As every other country after finishing its trade liberalization with its neighbors Kosovo will have to start to negotiate with the WTO since its membership is a prerequisite to join the EU. Rule of law is a very problematic issue which lacks some basic standards in this territory, until now this state responsibility was highly supported by the European Union Law Enforcement Mission in Kosovo (EULEX). Knowing this it is hard to understand why some basics of the WTO such as Intellectual property rights, Sanitary and Environmental issues are lagging far behind the WTO standards. As a non member of the UN Kosovo will have a specific status in negotiating with the WTO, certainly this will be determined mainly by the EU as it is under its interest sphere. Multilateral agreements for joining the WTO in this case will be determined mainly by negotiations with the EU. Certainly the outcome of this process will be in line with EU policies and WTO requirements as a constitutional and legal power. In this case EU will serve the function of the executive power in the system where WTO is a global trade authority. As an organization with the power to change state policies and laws the WTO will certainly reshape the Kosovo economy which will certainly be a benefit to its citizens and the end of illegal imports, sales and production.